Assessment of demonstration through yield and gap analysis of kharif groundnut in the different districts of West Bengal: ASSESSMENT OF DEMONSTRATION THROUGH YIELD AND GAP ANALYSIS OF GROUNDNUT - R KUNDU; S BISWAS; S JASH; G MOINUDDIN (Journal of Oilseeds Research, 2023)
Groundnut (Arachis hypogaea) is a popular source of oil and confectionery snack. Farmers of both tropical and subtropical regions grow groundnut to get high income. It has a good demand for its high nutritive value. This crop can be grown both in kharif and rabi seasons. In West Bengal conditions, small farmers prefer the varieties namely TG51 and TAG24. Five districts of West Bengal were taken under experiment during 2017 to 2021 (kharif season). A total 170 demonstrations were conducted in kharif, as per AICRP guidelines. Different percentage of gap was observed as a result of different practices like seed treatment, fertilizer management etc. In addition extension gap, technology gap etc. were calculated which showed a positive effect towards demonstration fields when compared to farmer’s own field. With the adoption of improved management practices and varieties through demonstration, farmers got 26.8% more average gross return and 30.5% more average net return in the demonstration field over the farmers’ fields.